2008
DOI: 10.1002/tea.20247
|View full text |Cite
|
Sign up to set email alerts
|

What do science teachers consider when selecting formative assessment tasks?

Abstract: The purpose of this qualitative exploratory study was to identify factors that influenced prospective and experienced secondary level science teachers' reasoning as they evaluated or selected tasks to formatively assess their students' understanding of scientific concepts. The analysis of the coded written responses revealed two categories of factors that influenced the teachers' reasoning: (1) characteristics of the task and (2) characteristics of students or the curriculum. Characteristics of the task relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 23 publications
2
19
0
2
Order By: Relevance
“…Recognizing the scarcity of research on science teachers' assessment reasoning, we became interested in better understanding the nature and development of secondary school science teachers' thinking in this area. For example, we have analyzed the factors that influence prospective and experienced science teachers' reasoning as they select tasks to formatively assess their students' understanding of scientific concepts (Tomanek, Talanquer, Novodvorky, ). Our work revealed that teachers' selection of assessment questions is largely influenced by the perceived cognitive demand and efficacy of the task, as well as by student characteristics such as perceived ability to answer a question.…”
mentioning
confidence: 99%
“…Recognizing the scarcity of research on science teachers' assessment reasoning, we became interested in better understanding the nature and development of secondary school science teachers' thinking in this area. For example, we have analyzed the factors that influence prospective and experienced science teachers' reasoning as they select tasks to formatively assess their students' understanding of scientific concepts (Tomanek, Talanquer, Novodvorky, ). Our work revealed that teachers' selection of assessment questions is largely influenced by the perceived cognitive demand and efficacy of the task, as well as by student characteristics such as perceived ability to answer a question.…”
mentioning
confidence: 99%
“…Given the scarcity of research in this area, our efforts in recent years have focused on better understanding the nature and development of secondary school science teachers' thinking about assessment. We have, for example, explored the main factors that influence prospective and experienced science teachers' reasoning as they select tasks to formatively assess their students' understanding of scientific concepts (Tomanek, Talanquer, & Novodvorsky, 2008). This analysis revealed that teacher thinking in this area seems to be largely influenced by characteristics of the assessment tasks related to cognitive demand and perceived efficacy (e.g., focus on targeted concepts), as well as by characteristics of the students, such as perceived ability to complete the assessment task.…”
mentioning
confidence: 99%
“…la plupart des études consultées, réalisées dans des domaines variés (par ex., sciences infirmières, astronomie, etc. ), révèlent que les étudiants disent aimer utiliser les télévoteurs en salle de classe (Meedzan & Fisher, 2009;sullivan, 2009). cependant, peu de recherches s'intéressant à la rétention de cet engouement chez les étudiants sont recensées.…”
Section: L'évaluation Formativeunclassified
“…un autre avantage non négligeable des télévoteurs est le fait que les réponses fournies par les étudiants sont anonymes (Fies & Marschall, 2006 ;sullivan, 2009 ;uhari, renko, & soini, 2003). Quand on demande aux étu -diants de répondre à une question à main levée, on ne garantit pas l'anonymat.…”
Section: L'anonymat Des Réponses Des éTudiantsunclassified